Automated office blood pressure is in agreement with awake and mean 24‐hour ambulatory blood pressure at the lower blood pressure range - Andreadis, Emmanuel A. (J Clin Hypertens (Greenwich), 2020)
Automated office blood pressure measurement eliminates the white coat effect and is associated with awake ambulatory blood pressure. This study examined whether automated office blood pressure values at lower limits were comparable to those of awake and mean 24‐hour ambulatory blood pressure. A total of 552 patients were included in the study, involving 293 (53.1%) men and 259 (46.9%) women, with a mean age 55.0 ± 12.5, of whom 36% were treated for hypertension. Both systolic and diastolic automated office blood pressures exhibited lower values compared to awake ambulatory blood pressure among 254 individuals with systolic automated office blood pressure <130 mm Hg (119 ± 8 mm Hg vs 125 ± 11 mm Hg, P < .0001 and 75 ± 9 mm Hg vs 79 ± 9 mm Hg, P < .0001 for systolic and diastolic BPs, respectively). Furthermore, the comparison of systolic automated office blood pressure to the mean 24‐hour ambulatory blood pressure levels also showed lower values (119 ± 8 vs 121 ± 10, P = .007), whereas the diastolic automated office blood pressure measurements were similar to 24‐hour ambulatory blood pressure values. Our findings show that when automated office blood pressure readings express values <130/80 mm Hg in repeated office visits, further investigation should be performed only when masked hypertension is suspected; otherwise, higher automated office blood pressure values could be used for the diagnosis of uncontrolled hypertension, especially in individuals with organ damage.